Motivation of Learner in Plant Science Program - Chathaokalor, Daovang; Sithivohane, Insavai; Salitxay , Timnoy; Briatia, Xoxiong (Souphanouvong University Journal Multidisciplinary Research and Development, 2016)
Understanding the learning behavior and realizing the motivation of student (learner) is apotential key for future developing, maintaining the stability of the plant Science program. This development program is also purpose to serve the qualified man power for local development in the future. This study aimed to know the motivation of the learners in Plant Science program. Questionnaires and surveying of the students (172 students under government and none-government quota who were studying in the program, and another 122 students who already graduated from the program was selected in this study. The surveying result from students who were studying in the program (172 people) showed that, most of the students has origin from Luangprabang province (76 people or 44.18%) where, the 15, 11, 6, 4, and 1 person came from Oudomxay, Xayaboury, Xiengkhouang, Luangnamtha, Champasak, and Phongsaly province, respectively.Lao lum had the highest number of students (50.5%), followed by Hmong and Kumou with 26.74 and 22.67%, respectively. According to the surveying result, most of learners came from medium family status (116 people or 67.4%). Whereas, 25.5% and 1.16% of the students came from poverty and rich family status, respectively. In addition the result showed that, students (101 people or 58.78% ) were non-government quota and paid for tuition fee them self. In the other hands, Plant Science program was selected as the main course to study from 59 students (58.4%).In among the motivation for the learners, social motivation has the highest rate (3.99), followed by working requirement, personal preference, and economic consideration (income) with the motivation rate of 3.69, 3.35, and 3.29, respectively. The result of surveying from the graduated students (122 students) referred that, students choose to work as government officer (54.91%) rather than working with private enterprise, private company, private business, and working on farm with 26.22, 7.37, ​2.45, and 9.01%, respectively. The highest income was ranged from 4,400,000-4,900,000LAK/​month (4.91%). Whereas, the lowest income was ranged from 1,400,000-1,900,000 LAK/​month (37.74%).